Collaborative application of the food sustainability assessment framework (FOODSAF) to transform food systems and farmer livelihoods in Makueni County, Kenya - Stellah Mikalitsa Mukhovi; Chinwe Ifejika Speranza; Boniface Kiteme; Aymara Zonta LIanque (PLoS ONE, 2026)
Food systems in arid and semi-arid lands face challenges that hinder them from meeting the food needs of communities and sustaining environmental resources. Using a collaborative approach between multiple societal stakeholders and academic actors, we applied the Food Sustainability Assessment Framework (FOODSAF) and a gender-differentiated participatory process in three workshops in Kenya involving women and men farmers, and social actors from the government, civil society, and private sector. The objectives of the study were to; a) assess the food sustainability of the Makueni agro-pastoral food system, b) assess the extent to which policies and practices of government, private sector, and civil society actors provide for an enabling or dis-enabling environment for farmers to achieve food sustainability, c) evaluate stakeholders perspectives of food sustainability indicators and identify areas in the food system that require intervention. The data were collected using workshops with farmers, policy implementers, private sector, and civil society actors, and analysed using descriptive analysis. The results show disparity in assessment of indicators by different stakeholders reflecting their perspectives, interests, experiences, and knowledge about each food system indicator. The performance of the value chain, the capacity of the food system to process and store food, and social self-organisation received the lowest scores and hence formed the basis for further reflection and collective action. This study shows that collective action supported by empirical evidence and collaborative considerations with stakeholders can contribute to the transformation of food systems and the associated farmer livelihoods. More collective actions are required to solve structural problems that smallholder farmers are incapable of negotiating individually.